Evaluation of entomopathogenic nematodes against diamond back moth, Plutella xylostella (Lepidoptera: Plutellidae) on cabbage under laboratory and glasshouse conditions - Tolera, G.; Hailu, T.; Dawd, M.; Negeri, M.; Selvaraj, T. (International Journal of Agricultural Technology, 2016)
Diamondback moth (DBM) (Plutella xylostella L., Lepidoptera: Plutellidae) is one of the most serious pest of cruciferous crops and causes huge economic losses. This study emphasized on determination of efficacy on EPN isolates against DBM larvae and also to evaluate the selected isolates of Entomopathogenic nematodes (EPN) for the control of DBM in cabbage plants under pot culture. Bioassay was conducted on three isolates of Stienernema (HI, AW3 and HH) and two isolates of Heterorhabdtis spp. (AEH and Z9). All 5 Ethiopian EPN were tested in single dose efficacy experiment (400IJ/ml) under laboratory condition. The result indicates that among the EPN isolates, HI (33.33, 56.67 & 82.64) and AEH (26.67, 63.33 & 91.67) EPN isolates produce highest mortality in the 24, 48 and 72hrs after treatment application. The most effective or virulent EPN isolates were further tested for their potential on DBM on pot planted cabbage infested with 3rd instars larvae under glasshouse condition using HI and AEH were studied at 3 different concentration levels (300, 400 and 500 IJ/ml) including free control. The experimental result indicates that, HI (30, 54.81&72.6) and AEH (23.7, 44.44 & 71.52) at higher concentration levels (500 IJ/ml) produce higher mortality after 24, 48 and 72hrs treatment applications as compared to other concentration levels.The relative potency values indicated that Steinernema spp. (HI (1, 1)) was more effective than Heterorhabditis spp. (AEH (1.21, 1.77)) in potency against 3rd instar larvae of DBM at the LC50 and LC90 level, respectively. From the Current study, it can be revealed that, Steinernema spp. (HI) and Heterorhabditis spp. (AEH) was found promising isolate which is also recommended for further field application study to control DBM.